(untitled) (Samriddhi Journal of Development Studies, 2022)
This paper sheds light in understanding the socio-cultural determinants for school dropout among adolescent girls in Dhanusha and Rautahat districts of Nepal. This study employed a mixed method approach to explore the reasons for dropout. The finding derived a conclusion that discriminatory gender norms, and traditional beliefs and practices lead girls to drop out. The research suggests traditional beliefs regarding women as wives with majority of the domestic responsibilities and early marriage limit their educational opportunities. Additionally, restricted mobility and lack of autonomy, and menstrual stigma also leads to school dropout. This study therefore aims to illuminate the importance of understanding these underlying factors in order to work towards creating a supportive environment that promotes girls’ autonomy, and agency within their household, and communities.